(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The space of the city as a porous and fertile locus is a powerful inducer for theatricalities. This article is the result of experiences practiced in the urban space, in which poetic, aesthetic, and political gaps and fissures were opened, all experienced during the IV Brecht and Education Forum. Utilizing Brecht on this space, exploring its textual materials, articulated with the procedures of Theatre Games, was established as a collaborative process, giving rise to dramaturgical possibilities that the city offered when occupied by a group that proposed to walk through, observe, and feel it.